Trend of alcohol use among adolescents and the relation with demographic, environmental and psychological factors - Selly Jaimon; Pravina Deligannu; Fredie Robinson (Universiti Putra Malaysia, 2023)
Annually, the harmful use of alcohol contributes to approximately 3.3 million deaths globally, with 4.6% of alcohol-related mortality and 4.0% of the burden of disease and injury in Southeast Asia. Adolescence is an essential stage of a child’s development transitioning into adulthood. During this time, adolescents are vulnerable to various social issues that can impact their well-being and development, experimenting with alcohol among others. This review explores the alcohol consumption trend among adolescents and the factors associated, particularly in Malaysia. There are not many studies that explored alcohol use and the associated factors. This partially is attributed to policies restricting alcohol use for adolescents and that it is a sensitive issue for certain communities. Though, adolescents who are current drinkers made up 11.1% of the drinking population with significantly higher consumption in males (15.8%) than females (6.2%). The three prime factors influencing alcohol use among adolescents are socio-demographic, environmental and psychological. Hence, policies on alcohol reduction should be developed for adolescents specifically in school and programmes addressing family functioning taking account of local settings appropriateness.